Pengaruh Suasana Toko, Kualitas Pelayanan dan Layout terhadap Keputusan Pembelian pada Sambi Swalayan - Linda Linda; Baju Pramutoko; Ustadus Sholihin (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study discusses the effect of store atmosphere, service quality, and layout on purchasing decisions at Sambi Swalayan. This study uses quantitative methods with the aim of knowing the extent to which these three variables influence consumer decisions in making purchases. The research sample was obtained using the Accidental Sampling technique, which is a sampling technique based on chance, where the researcher chooses respondents who are accidentally encountered at the research location and deemed suitable for sampling. The number of respondents obtained in this study was 99 people. In data processing, researchers use several statistical analysis techniques, including validity and reliability tests to test the accuracy and consistency of research instruments. In addition, a classical assumption test was carried out to ensure that the data met the requirements for regression analysis, then continued with multiple linear regression analysis to determine the relationship and influence between variables. The coefficient of determination (R²) is used to see how much the independent variable contributes to the dependent variable, while the t test and f test are used to test the effect partially and simultaneously.The results showed that the store atmosphere had a significant effect on purchasing decisions with a sig value. 0,000 < 0,05. Conversely, service quality has no significant effect because the sig value. 0,383 > 0,05. However, store layout has a significant influence on purchasing decisions with a sig value. 0,000 < 0,05. Simultaneously, the three variables have a significant effect on purchasing decisions at Sambi Swalayan with a sig value. 0,000 < 0,05.